The Value of Radionuclide Cisternography in a Case of Spontaneous Cerebrospinal Leak - Barral, Carlyle Marques; Lemos, Thaís Ribeiro; Nunes, Shirleide Santos; Sanches, Sandra Monetti Dumont (World Journal of Nuclear Medicine, 2022)
Spontaneous intracranial hypotension (SIH) is an infrequent cause of daily persistent orthostatic headache with an incidence of 5 to 100,000 persons/year. In very rare cases, no cause can be found and these conditions may be called spontaneous cerebrospinal fluid leak (CSFL). Radionuclide cisternography (RNC) has played useful role in detecting CSFL. Although RNC has been used in many cases, few have been reported in which CSFL out of the subarachnoid space was detected. A case of CSFL confirmed by RNC direct findings is reported. SIH is difficult to diagnose and 95% of patients may initially receive an incorrect diagnosis. RNC has been shown to be fairly characteristic in SIH patients.
Keywords: spontaneous intracranial hypotension; spontaneous cerebrospinal fluid leak; orthostatic headache; Tc 99m-DTPA